2017
DOI: 10.5004/dwt.2017.20702
|View full text |Cite
|
Sign up to set email alerts
|

A novel thiocarbohydrazide derivative for preconcentration of copper(II), nickel(II), lead(II), and cadmium(II) in water samples for flame atomic absorption spectrophotometry (FAAS)

Abstract: a b s t r a c tA preconcentration procedure has been developed by using a thiocarbohydrazide derivative (1,5-bis(phenylthiocarbamoyl)thiocarbohydrazide) as a novel sorbent. The ligand was synthesized and used for preconcentration of Cu(II), Ni(II), Pb(II), and Cd(II) ions from water samples by batch and column procedures to enrich metal concentrations appropriate for flame atomic absorption spectrophotometry (FAAS). The optimum pHs for effective solid-phase extractions were 5 and 7 for Cu(II), and Ni(II), Pb(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Figure 9 indicates the effect of pH on copper (II) and lead (II) removal efficiencies of the nano-clay and iron impregnated nanoclay. Copper (II) and lead (II) ions have the highest tendency to form a precipitate at alkaline conditions and be separated from an aqueous solution by a mechanism of chemical precipitation (Çetinkaya & Aydin, 2017; Pang et al, 2009). Pang et al (2009) reported an effective pH range of 7.8 to 8.8 and 6.3 to 11.1 for the highest lead hydroxide and copper hydroxide precipitations, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 9 indicates the effect of pH on copper (II) and lead (II) removal efficiencies of the nano-clay and iron impregnated nanoclay. Copper (II) and lead (II) ions have the highest tendency to form a precipitate at alkaline conditions and be separated from an aqueous solution by a mechanism of chemical precipitation (Çetinkaya & Aydin, 2017; Pang et al, 2009). Pang et al (2009) reported an effective pH range of 7.8 to 8.8 and 6.3 to 11.1 for the highest lead hydroxide and copper hydroxide precipitations, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Pang et al (2009) reported an effective pH range of 7.8 to 8.8 and 6.3 to 11.1 for the highest lead hydroxide and copper hydroxide precipitations, respectively. Also, an optimum pH of 5.0 to 7.0 was reported for Pb 2+ and Cu 2+ adsorption (Çetinkaya & Aydin, 2017). In this study, the experiment was conducted at lower pH (pH 3.0 and 5.0) to exclude the higher pH induced metal hydroxide precipitation (Pb(OH) 2 $ & Cu(OH) 2 $) and clearly understand the adsorbents activity without any intervention.…”
Section: Adsorption Of Cu 2+ and Pb 2+ Using Nano-clay And Iron Impre...mentioning
confidence: 99%
“…One of these problems is the interference effect of the complicated matrix and the other is that the lower levels of trace element than the detection limit of the utilized instrument. 13 In order to eliminate these drawbacks, it is indispensable to implement a traditional separation and preconcentration method such as solid phase extraction, 14 cloud point extraction, 15 liquid-liquid extraction 16 and coprecipitation 8 before the analyses step. Among these, coprecipitation is a powerful alternative due to its low cost, simplicity and rapidity, less usage of chemical reagents and obtaining high preconcentration factors in the method.…”
Section: Introductionmentioning
confidence: 99%